Pygopagus Conjoined Twins: A Neurophysiologic Intraoperative Monitoring Schema. Issue 2 (March 2017) - Cromeens, Barrett P.; McKinney, Jennifer L.; Leonard, Jeffrey R.; Governale, Lance S.; Brown, Judy L.; Henry, Christina M.; Levitt, Marc A.; Wood, Richard J.; Besner, Gail E.; Islam, Monica P.
Summary: Conjoined twins occur in up to 1 in 50, 000 live births with approximately 18% joined in a pygopagus configuration at the buttocks. Twins with this configuration display symptoms and carry surgical risks during separation related to the extent of their connection which can include anorectal, genitourinary, vertebral, and neural structures. Neurophysiologic intraoperative monitoring for these cases has been discussed in the literature with variable utility. The authors present a case of pygopagus twins with fused spinal cords and imperforate anus where the use of neurophysiologic intraoperative monitoring significantly impacted surgical decision-making in division of these critical structures.